Nitric oxide as a potent signalling molecule in plants - Erdei, László; Kolbert, Zsuzsanna (Acta Biologica Szegediensis, 2008)
The role of NO in stress responses in plants came in the focus of plant science in the last decade. Better understanding of plant stress responses is very important in the light of increasing intensities of stressors like drought, salinity and others, due to global climatic and environmental changes. Our knowledge, concerning signal transduction pathways is very scarce, especially in terms of NO-related alterations in proteins and gene expression as well as regulation. In this review we consider different NO-reactions, signalling pathways, NO – plant hormone interactions and NO-induced and -mediated signalization under osmotic stress in relation with the development of root architecture.